Does mammographic density remain a radiological challenge in the digital era?. (June 2021) - Al-Mousa, Dana S; Rawashdeh, Mohammad; Alakhras, Maram; Spuur, Kelly M; AbuTaimai, Rula; Brennan, Patrick C
Background: The low subject contrast between cancerous and fibroglandular tissue could obscure breast abnormalities. Purpose: To investigate radiologists' performance for detection of breast cancer in low and high mammographic density (MD) when cases are digitally acquired. Material and Methods: A test set of 60 digital mammography cases, of which 20 were cancerous, were examined by 17 radiologists. Mammograms were categorized as low (≤50%) or high (>50%) MD and rated for suspicion of malignancy using the Royal Australian and New Zealand College of Radiology (RANZCR) classification system. Radiologist demographics including cases read per year, age, subspecialty, and years of reporting were recorded. Radiologist performance was analyzed by the following metrics: sensitivity; specificity; area under the receiver operating characteristic (ROC) curve (AUC), location sensitivity, and jackknife free-response ROC (JAFROC) figure of merit (FOM). Results: Comparing high to low MD cases, radiologists showed a significantly higher sensitivity ( P  = 0.015), AUC ( P  = 0.003), location sensitivity ( P  = 0.002), and JAFROC FOM ( P  = 0.001). In high compared to low MD cases, radiologists with <1000 annual reads and radiologists with no mammographic subspecialty had significantly higher AUC, location sensitivity, and JAFROC FOM. Radiologists with ≥1000 annual reads and radiologists with mammography subspecialty demonstrated a significant increase in location sensitivity in high compared to low MD cases. Conclusion: In this experimental situation, radiologists' performance was higher when reading cases with high compared to low MD. Experienced radiologists were able to precisely localize lesions in breasts with higher MD. Further studies in unselected screening materials are needed to verify the results.